Comparative study of microorganisms in soil of trunking and non-trunking sago palms plantation - Wong, Ming Kui (Universiti Malaysia Sarawak (UNIMAS), 2004)
Sarawak is the principal exporter of sago starch to the world market, exporting about 25 000 - 30 000 tonnes of sago starch annually. Commercialization of the sago industry and plantation could ensure the production of sago starch in large quantity and of homogeneous quality. Hence LCDA (Land Custody and Development Authority of Sarawak) developed the world's first commercial deep peat sago plantation in Mukah, Sarawak in the year 1987, with minimal management intervention. However, most ofthose sago palms planted are not showing any sign of trunking after 10 years old. Moreover, they suffered stunted growth and high mortality rate. This study is a part ofan umbrella study looking into factors influencing the growth patterns of sago palms under minimally managed peat swamp cultivation in Dalat and Mukah. This study applies a comparative-inductive study design to compare selected soil physicochemical and microbiological parameters, such as soil pH, soil CO2 emission and soil microbiota, focusing on mycorrhizae and N2 fixers, of soil samples collected from trunking and non-trunking sago palms. Two sampling plots were identified and subjected to further study, they are Block 1 (as trunking block) and Block 7 (as non-trunking block) ofDalat Sago Plantation (DSP) Phase lA. Sago trunk volume was used as the index oftrunking. It was found that DSP was completely water-logged during the duration ofthe study (September, 2003 - January, 2004) and that its peat soil was very acidic (dry soil pH, 2.82 - 3.13). Moreover, the soil pH for trunking block (2.98) was marginally higher than nontrunking block (2.90) (p =0.0667). Using a field method ofC02 detection by soda lime absorption, soil C02 emission for trunking block (3.5 g COJ! m21day) was also found to be significantly higher than non-trunking block (2.1 g C021 m21day) (p = 0.0127). Total recoverable viable aerobic bacteria (TRVAB) count has been enumerated using standard plate count method and this study is 80.46 % confident (only marginally significant) that TRVAB count for trunking block (9.8 x 105 cful g dry soil) was higher than non-trunking block (7.2 x 105 cful g dry soil). Attempts at quantifying degree of mycorrhizal infection using gridline-intersect method were unsuccessful due to the inability of the technique to distinguish between living and non-living roots. Enumeration oftolal aerobic N2 fixers (TANF) using standard plate count method did not reveal any significant difference between the TANF count for trunking (9.1 x 105 cful g dry soil) and non-trunking block (8.2 x lOS cful g dry soil). This suggested that most of the soil bacteria quantified were aerobic N2 fixers which were probably inactivated by the water-logging condition. Only one colony of anaerobic N2 fixers was isolated. Regression and Partial Correlation Analysis have proven that all the soil microbiological parameters were related to the trunk volume of the sago palm (l = 1.000,p = 0.008). TRVAB was found to be the most influential parameter. However, it was undermined by the high level of soil acidity. Therefore, under existing natural field condition, soil pH seemed most important in affecting trunk volume. In light of these results, two soil amendment strategies are suggested, i.e. the improvement of soil aeration by lowering the water table and increasing the soil pH by liming. However, soil microbiological interactions are so complex that the actual consequences of these amendments though very influential and significant, are quite unknown without further in-depth study into the subject. Therefore it is high time that the effects ofsoil microorganisms on the growth of sago palms be subjected to intensive research since proper understanding of soil microbiology would benefit XII the plantation as well as the natural environment because microbiological amendments on the soil are as a rule, environmentally-friendlier and less capitalintensive.